STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN DAYA TARIK SEKOLAH DAN JUMLAH PESERTA DIDIK BARU DI SMP SWT YAYASAN PERGURUAN UTAMA - Astika, Lilis; M Solih; Nurul Anjani Daulay (Cemara Education and Science, 2024)
This research was conducted to find out the principal's strategy in increasing the attractiveness of the school and the number of new students at SWT Primary School Middle School. This research uses a qualitative method, namely a research approach that focuses on understanding phenomena based on the perspective of the subject being studied. This research uses observation and interview techniques. The results of this research show that the main strategy used to increase the school's attractiveness and the number of new students involves active promotion and physical improvement of the school. Promotion is carried out directly by visiting the homes of elementary school graduates and using social media intensively. Apart from that, efforts to improve school facilities are also considered important to attract new students.